Student Perceptions of a Cloud Assessment Learning Environment - Rickards, Anthony; Steele, A. (Association for the Advancement of Computing in Education (AACE), 2014)
This paper describes a multi-method study conducted at a New Zealand polytechnic which investigated student perceptions of a cloud assessment learning environment. Factors examined included teacher-student interpersonal behaviour, conceptual change, student achievement, attitude and computing confidence. This unique study provides a clear insight into student perceptions of the cloud assessment learning environment. Educators will be able to utilise data from this study to better prepare students, manage expectations, and emphasise positive aspects of their own classroom learning environment.